Research on Extreme Weather Prediction Based on ARIMA Modeling - Lu, Yi; Luo , Dezhi; Yang, Xi (Transactions on Computer Science and Intelligent Systems Research, 2024)
The greatness of nature is often astounding, but few people realize that behind its greatness lies a host of impacts from extreme weather, and with global climate change continuing to intensify, it poses unprecedented challenges to the property insurance industry. In this paper, we develop a broadly applicable risk scoring model that provides the property insurance industry with critical insights for more accurate risk assessment and adjustment of underwriting strategies. In this paper, we use an ARIMA model to predict the expected annual losses from extreme weather hazards in different regions, and based on this, we develop a premium calculation model to ensure that insurers can cover compensation costs and realize expected profits.